2019
DOI: 10.3390/jcm8020185
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Electrospun Scaffolds for Endothelialization of Tissue-Engineered Vascular Grafts Using Human Cord Blood-Derived Endothelial Cells

Abstract: Tissue engineering has gained attention as an alternative approach for developing small diameter tissue-engineered vascular grafts intended for bypass surgery, as an option to treat coronary heart disease. To promote the formation of a healthy endothelial cell monolayer in the lumen of the graft, polycaprolactone/gelatin/fibrinogen scaffolds were developed, and the surface was modified using thermoforming and coating with collagen IV and fibronectin. Human cord blood-derived endothelial cells (hCB-ECs) were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 103 publications
1
10
0
2
Order By: Relevance
“…Our constructs showed pore sizes between 0.08 ± 0.01 µm 2 and 0.12 ± 0.05 µm 2 , which lies in the range of a native vessel. Several studies have already described that FN improves the endothelialization of vascular grafts [19,48,49,51]. In our study, we observed a fibrous-like structure of the coated FN (Figure 3b).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our constructs showed pore sizes between 0.08 ± 0.01 µm 2 and 0.12 ± 0.05 µm 2 , which lies in the range of a native vessel. Several studies have already described that FN improves the endothelialization of vascular grafts [19,48,49,51]. In our study, we observed a fibrous-like structure of the coated FN (Figure 3b).…”
Section: Discussionsupporting
confidence: 73%
“…It is of interest with regard to endothelialization, as it plays a pivotal role in wound healing [45,46]. Several studies described the coating of FN in combination with collagens type I [47] and type IV [48], with fibrinogen and tropoelastin [49], hepatocyte growth factor [50], heparin, Cells 2020, 9,778 3 of 29 and VEGF [51] and with SDF-1α [19] to improve reendothelialization. However, it has never been used in combination with DCN before.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as another important ingredient of ECM, FN play a key role in promoting cell adhesion, proliferation and signal transduction. Ardila et al believed that the FN is an active ingredient in stimulating the formation of ECs lumen, while other ECM molecules will only provide the necessary ingredients for the environment [26]. Therefore, in this study we used stem cell-derived cell sheets that provided the native ECM components to study the interaction between ECM microenvironment and ECs.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 could promote the differentiation of MSC to the myogenic lineage and enhance mechanical properties of the vascular constructs. The results revealed that the conjugation of TGF-β1 in a 3D fibrin matrix induced the activated Smad2 signal in fibrin-embedded cells for several days, leading to an increased vascular contractility [31,32].…”
Section: Biomimetic Materials For Tissue Regenerationmentioning
confidence: 99%